Implementasi Seni Hadrah sebagai Media Motivasi Beragama bagi Usia Anak di dusun Parimono Jombang - Assadili, Hilmi Hasan; Slamet, Moh. (Menara Tebuireng, 2024)
There are 3 (three) focuses of this research, namely (1) How is the implementation of hadrah art as a religious motivation medium for children of Parimono Hamlet, Jombang Regency? (2) How does the community of Parimono Hamlet respond to the implementation of hadrah art as a medium to increase religious motivation for children? (3) What is the role of hadrah art as a medium to increase religious motivation for children of Parimono Hamlet, Jombang Regency? To answer this problem, the method used is a qualitative method with a descriptive approach. In this study, it can be concluded that the implementation of hadrah art is very effective for early childhood through hadrah art activities, children can learn about religious values, traditions, and religious practices through interesting art. The community's response to the art of hadrah is very positive, with the existence of the art of hadrah the community is very helpful in educating their children in learning and applying religious teachings practically. The role of hadrah art plays a role as a means of encouraging children in Parimono Hamlet to be more actively involved in religious practices.   Keyword: Hadrah Art, Religious Motivation, Children